2007
DOI: 10.2217/17460751.2.4.383
|View full text |Cite
|
Sign up to set email alerts
|

Xenogenic Bone Matrix Extracts Induce Osteoblastic Differentiation of Human Bone Marrow-Derived Mesenchymal Stem Cells

Abstract: Colloss and Colloss-E are sterile acellular lyophilizates extracted from bovine and equine bone matrix, respectively. Animal and clinical studies have shown that these xenogenic bone matrix extracts (BMEs) are effective as bone graft substitutes. In this report, we investigated the effect of Colloss and Colloss-E on human adult in vitro-expanded bone marrow-derived mesenchymal stem cells (BMMSCs). Specifically, we assessed whether these xenogenic BMEs induced osteoblastic differentiation of cultured BMMSC. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 41 publications
3
22
0
Order By: Relevance
“…By culturing human mesenchymal stem cells over-expressing human telomerase reverse transcriptase (hMSC-TERT) in plates coated with BPE at different concentrations, Woo et al [61] demonstrated that BPE could increase the proliferation of undifferentiated hMSC-TERT cells and accelerate osteoblastic differentiation of hMSC-TERT cells with a limited effect on proliferation. It was also observed by El-Sabban et al [66] that BPE could induce osteoblastic differentiation of in vitro expanded BMSCs.…”
Section: Stem Cell Interactionsupporting
confidence: 53%
“…By culturing human mesenchymal stem cells over-expressing human telomerase reverse transcriptase (hMSC-TERT) in plates coated with BPE at different concentrations, Woo et al [61] demonstrated that BPE could increase the proliferation of undifferentiated hMSC-TERT cells and accelerate osteoblastic differentiation of hMSC-TERT cells with a limited effect on proliferation. It was also observed by El-Sabban et al [66] that BPE could induce osteoblastic differentiation of in vitro expanded BMSCs.…”
Section: Stem Cell Interactionsupporting
confidence: 53%
“…This has raised the question of whether adjuvant therapies with BMPs mainly raise the overall bone turnover at its application site, rather than favoring an anabolic increase in new bone formation (Little et al 2007). Colloss E contains trace amounts of bone growth factors embedded within the lyophilized collagen (van der Zande et al 2006, El-Sabban et al 2007. No conclusions on optimal dose, release rate, or growth factor combinations can be made based on this study.…”
Section: Discussionmentioning
confidence: 90%
“…This natural material, similar to those of the human bone, shows great osteoconductive properties [6]. There are a few studies on equine-derived bone substitutes [7,8] for filling the bone gap. The material used in the present study was an equine-derived bone substitute material commercially available (Osteoplant-Flex, Bioteck Srl, Arcugnano, Vicenza, Italy), which was deantigenated through a low-temperature (max 37°C) enzymatic process that should not alter its mineral component.…”
Section: Original Papersmentioning
confidence: 99%